Resepsi Performatif dalam Tradisi Mabbuddu' - Fadhilah Nur Khaerati; Muflihah Muflihah; Nurul Azkiya; Aurelia Primandita; Nurul Mutawadhiah Yunus (SUHUF, 2025)
This research aims to analyze the implementation of the mabbuddu' tradition in Wajo District and the reception of the living Qur'an and hadith in the mabbuddu' tradition in its position as a religious expression and providing financial benefits. This research is a field study using a qualitative phenomenological approach. Data was obtained from observation, interviews and documentation. Researchers interviewed several sources including tahfiz students, tahfiz coaches/religious figures and the community. Data analysis was carried out using the descriptive-analysis method by Miles, Huberman, and Saldana, then further analysis was carried out using the theory of the living Qur'an and hadith as an analytical tool to find the final conclusion. The findings of this study reveal that, in its development, the reception of the living Qur’an and Hadith in the mabbuddu’ tradition has generated two principal meanings: (1) a religious expression in the form of prayers and the offering of rewards to the deceased, and (2) a socio-economic function that provides financial benefits through charity and support for the community as well as Qur’an memorization students (santri tahfiz).